2010
DOI: 10.1007/s10533-010-9432-7
|View full text |Cite
|
Sign up to set email alerts
|

Variations in microbial isotopic fractionation during soil organic matter decomposition

Abstract: International audiencehe soil microbial biomass (SMB) is known to participate in key soil processes such as the decomposition of soil organic matter (SOM). However, its contribution to the isotopic composition of the SOM is not clear yet. Shifts in the 13C and 15N natural abundances of the SMB and SOM fractions (mineralised, water soluble and non-extractable) were investigated by incubating an unamended arable soil for 6 months. Microbial communities were also studied using Fatty Acid Methyl Ester specific iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
59
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 70 publications
8
59
1
Order By: Relevance
“…3). However, Lerch et al (2011) found fractionation to vary over time when calculated in this manner, and while changes in substrate could account for this pattern it is also likely that the active microbial community is changing. Fast changes in microbial composition have been documented after addition of labile substrate (Cleveland et al, 2007), rapidly changing environmental conditions (Gordon et al, 2008), and other environmental stresses (Schimel et al, 2007).…”
Section: Fractionation Due To Microbial Metabolismmentioning
confidence: 89%
See 2 more Smart Citations
“…3). However, Lerch et al (2011) found fractionation to vary over time when calculated in this manner, and while changes in substrate could account for this pattern it is also likely that the active microbial community is changing. Fast changes in microbial composition have been documented after addition of labile substrate (Cleveland et al, 2007), rapidly changing environmental conditions (Gordon et al, 2008), and other environmental stresses (Schimel et al, 2007).…”
Section: Fractionation Due To Microbial Metabolismmentioning
confidence: 89%
“…For example, the use of positional labeling of carbon in glucose has given metabolic insight into carbon pathways in mycorrizhae (Scandellari et al, 2009). Studies that assess the isotopic composition of soil microbial biomass usually treat soil microbes as a single C pool without differentiating between metabolically active and dormant microorganisms (Santrûcková et al, 2000;Lerch et al, 2011). Soil microbial biomass is composed of both active and dormant microorganisms, yet, CO 2 respired from microorganisms derives solely from those that are metabolically active (Stenstrom et al, 2001;Kuzyakov, 2008, 2009;Millard et al, 2010;Werth and Kuzyakov, 2010).…”
Section: Synthesis/ Remobilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, numerous observations showed that plant compounds are slightly depleted in 13 C and 15 N compared to bulk SOM. Lerch et al (2011) tested the assumption according to which fractionation accompanying microbial metabolism may be at the origin of this enrichment of SOM (Balesdent and Mariotti 1996;Bird et al 2003;Dijkstra et al 2006). They quantified 13 C and 15 N fractionation factors between soil and microbial biomass and confirmed that microbial isotopic fractionation leads to the enrichment of SOM in heavy isotopes.…”
mentioning
confidence: 97%
“…The depletion in carbon isotope values may be due to 482 several factors, including changes in the ratio of C 3 and C 4 plants on the landscape, changes in 483 the growing conditions of plants (such as canopy structure, and water or nutrient stress), changes 484 in the ratios of isotopically distinct organic fractions in the sediment organic matter, and changes 485 in organic inputs from microorganisms in soils (Tieszen 1991 cooler/dryer conditions indicated by a decrease in magnetic susceptibility occurring at KTC at 504 the same time. However, the trend in δ 13 C values at KTC is relatively low magnitude, and 505 isotopic fractionation and microbial activity cannot be fully dismissed as contributing factors 506 (Lerch et al 2011;Schweizer et al 1999;Tieszen 1991;Wynn 2007). Carbon isotope values of 507 leaf wax n-alkanes may help to overcome these ambiguities because these are more diagnostic 508 than those from bulk sediments, which contain materials of both terrestrial and aquatic origin.…”
mentioning
confidence: 99%